The association between fatty acid quality indices and quality of life among overweight and obese women: A cross-sectional study - Rasaei, Niloufar; Daneshzad, Elnaz; Soveid, Neda; Clark, Cain C. T.; Mirzaei, Khadijeh (Frontiers in Public Health, 2023)
Background Reduced quality of life (QOL) is a major public health challenge affecting the global population. Fatty acid quality indices (FAQIs) are novel determinants of QOL and may impact various aspects of QOL. Prior research has established a significant link between dietary habits and QOL. However, the association between FAQIs and specific dimensions of QOL has not been established. Therefore, we aimed to investigate the association between FAQIs and QOL in overweight and obese women. Methods In total, 378 adult overweight or obese women participated in this cross-sectional study. Several anthropometric indices, systolic and diastolic blood pressure, and biochemical factors were measured using standard protocols. Dietary intake was assessed using a validated and reliable semi-quantitative food frequency questionnaire (the FFQ, 147 items). The cholesterol–saturated fat index (CSI) and the ratio of omega-6/omega-3 (N6/N3) essential fatty acids consumed were employed as FAQIs. The SF-36 questionnaire was administered to measure QOL. Linear logistic regression was used, in the form of raw and adjusted models, to evaluate the associations between FAQIs and QOL. Results The study sample consisted of 279 participants for whom ω-6/ω-3 ratio was measured and 378 participants for whom CSI was measured. The mean (±SD) age of participants was 36.65 ± 9.07 years. Linear logistic regression, with adjustment for potential confounders, such as age, energy intake, body mass index, employment, and thyroid status, indicated that ω-6/ω-3 intake ratio was negatively and marginally significantly associated with general health (β = −139.94, 95% CI: [−286.54, 6.66]; p = 0.061) and physical role limitations (β= −337.68, 95% CI: [−679.99, 1.61]; p = 0.051). A significant negative association was observed between ω-6/ω-3 intake ratio and social functioning (β = −247.54, 95% CI: [−458.14, −36.94]; p = 0.021), which indicates that obese and overweight women with a higher ω-6/ω-3 intake ratio obtained lower scores on social functioning. Conclusions It was found that FAQI scores were negatively associated with certain QOL measures among overweight and obese Iranian women, suggesting that a higher consumption of fatty acids, especially trans and saturated fatty acids, may be associated with lower QOL.